Two new potamid crabs, Yuexipotamon arcophallus new genus, new species and Minutomon shanweiense new genus, new species, (Crustacea: Decapoda: Brachyura: Potamidae) from southern China - Huang, Chao; Mao, Si Ying (Zootaxa, 2014)
Two new Chinese genera and species of freshwater crabs, Yuexipotamon arcophallus, new genus, new species, and Minutomon shanweiense, new genus, new species, are described from Zhaoqing City and Shanwei City, respectively. The former is superficially closest to Huananpotamon Dai & Ng, 1994, while the latter resembles Sinopotamon Bott, 1967, and Mediapotamon Dai, 1995. The two new genera, however, possess distinctive combinations of carapace, third maxilliped, male thoracic sternal and first gonopodal characters that easily distinguish them from other genera. Notes on the general biology of the two new species are also given.